(untitled) (Research, Society and Development, 2022)
The use of new natural antimicrobials has gained attention from the pharmaceutical and food industry, in addition to end consumers, as additive options to conventional antibiotics for resistant microorganisms and also as natural preservatives. Essential oils are secondary plant metabolites that protect plants against predators and pathogens. The aim of this study was to evaluate thermal properties of cinnamon essential oil (EO) and its antibacterial activity. Ten components were identified, with (E) - cinnamic acid (67.70%) being the major component. Cinnamon EO was thermally stable up to 106.6ºC (Tonset) and Tdec occurred at 178.5 °C and Toffset up to 216.0 °C. There was endothermic transition; enthalpy variation (∆H) and activation energy (Ea) was -531.6 KJ Kg-1 and -1.26 ± 0.03 J mol-1, respectively. Bacterial strains showed distinct resistance to tested antibiotics and variation in Minimum Inhibitory Concentration values ranging from 0.8 to 1.6 mg mL-1. Cinnamon EO initiated bactericidal effect against all bacteria tested after four hours of contact and Minimum Bactericide Concentration was 0.4 mg mL-1, exception for Bacillus cereus (0.8 mg mL-1). Analysis of cinnamon thermal properties EO showed its stable thermal performance up to 106.6 °C and broad spectrum, that may be an antimicrobial proposal.